Monte Carlo [videorecording (DVD)] - Bezucha, Thomas; Bezucha, Thomas; Gomez, Selena, 1992-; Cassidy, Katie, 1986-; Meester, Leighton, 1986-; MacDowell, Andie (20th Century Fox Home Entertainment, 2011)
Get ready for an awesome adventure of a lifetime in Monte Carlo! Grace, a high-spirited high school grad, is looking forward to a vacation in Paris with her best friend Emma and stepsister Meg. Just as the girls think their trip is ruined when their hyperactive tour guide leaves them behind, Grace is mistaken for a wealthy socialite and the trio is whisked away to Monte Carlo for a thrilling week of glitz, glam, and unforgettable fun.